Streptococcus suis surface-antigen recognition by antibodies and bacterial elimination is influenced by capsular polysaccharide structure - Dolbec, Dominic; Lehoux, Mélanie; Okura, Masatoshi; Takamatsu, Daisuke; Gottschalk, Marcelo; Segura, Mariela (Frontiers in Cellular and Infection Microbiology, 2023)
Streptococcus suis is an encapsulated bacterium causing severe diseases in swine. Here, we compared the protective properties of the capsular polysaccharide (CPS) of different S. suis serotypes by using serotype-switched mutants in a mouse model of infection. CPS structure influenced bacterial survival in mice, antibody binding, and antibody-mediated bacterial killing. The CPS of serotypes 3, 4 and 14 allowed more antibody binding and bacterial elimination than the CPS of serotypes 2, 7 and 9. Results suggest that the different CPS structures of S. suis provide varying levels of protection by influencing antigen availability and elimination by the host immune system.